1994
DOI: 10.1128/mcb.14.1.822
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the second largest subunit of TFIIIC increases a rate-limiting step in transcription by RNA polymerase III.

Abstract: In previous studies, we have shown that the PCFI-I mutation of Saccharomyces cerevisiae suppresses the negative effect of a tRNA gene A block promoter mutation in vivo and increases the transcription of a variety of RNA polymerase III genes in vitro. Here, we report that PCF1 encodes the second largest subunit of transcription factor IIIC (TFIIIC) and that the PCFI-1 mutation causes an amino acid substitution in a novel protein structural motif, a tetratricopeptide repeat, in this subunit. polypeptide is the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
72
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 39 publications
0
72
0
Order By: Relevance
“…Eight TPRs are needed for formation of trimers, and the trimerization is further stabilized by the presence of the full complement of 11 TPRs. Previous work has demonstrated that individual TPRs are responsible for mediating specific protein-protein interactions (26,27), so it is possible that additional studies will delineate the TPR requirements into individual TPRs. Although a portion of the TPR domain is clearly responsible for OGT subunit interactions, it may also serve as a protein interaction domain for effector proteins that regulate the activity or substrate specificity of the enzyme.…”
Section: The P110 Subunit Is the Catalytic Subunit Of The Ogt-mentioning
confidence: 99%
See 1 more Smart Citation
“…Eight TPRs are needed for formation of trimers, and the trimerization is further stabilized by the presence of the full complement of 11 TPRs. Previous work has demonstrated that individual TPRs are responsible for mediating specific protein-protein interactions (26,27), so it is possible that additional studies will delineate the TPR requirements into individual TPRs. Although a portion of the TPR domain is clearly responsible for OGT subunit interactions, it may also serve as a protein interaction domain for effector proteins that regulate the activity or substrate specificity of the enzyme.…”
Section: The P110 Subunit Is the Catalytic Subunit Of The Ogt-mentioning
confidence: 99%
“…Further examination of the protein sequence indicate that p110 can be divided into two distinct domains, the aminoterminal half of the protein containing multiple tetratricopeptide repeats (TPRs) and the carboxyl-terminal half of the protein representing a novel polypeptide believed to contain the catalytic portion of the enzyme. TPRs are found in a large number of proteins of diverse function and play a role in modulating a variety of cellular processes, including cell cycle (22)(23)(24), transcription regulation (25)(26)(27), and protein transport (28) by mediating specific protein-protein interactions (reviewed in Refs. 29 and 30).…”
mentioning
confidence: 99%
“…In particular, mutations in and around TPR2 have been shown to increase transcription in vivo of a tRNA gene bearing a defective A block (24,25). The same mutations have also been shown to increase transcription of wild-type and mutant templates in vitro by facilitating the recruitment of TFIIIB70 (25).…”
mentioning
confidence: 99%
“…Subsequent binding of the TBP and Bdp1 subunits of TFIIIB generates a series of structural changes in Tfc4, Brf1 and DNA that leads to progressively increased accessibility of Brf1 to DNA (8). The protein-protein interactions between TFIIIB subunits, together with DNA bending, generate a highly stable TFIIIB complex, a structure that surrounds and kinetically traps the DNA (9 -12).Tfc4 contains eleven copies of a ubiquitous protein-protein interaction motif known as a tetratricopeptide repeat (13,14).TPR motifs, as the name implies, are typically 34 amino acids in length and fold into two antiparallel ␣-helices (designated A and B, Ref. 15).…”
mentioning
confidence: 99%
“…Tfc4 contains eleven copies of a ubiquitous protein-protein interaction motif known as a tetratricopeptide repeat (13,14).…”
mentioning
confidence: 99%